Prognostic Significance of Immunohistochemical Markers and Genetic Alterations in Malignant Peripheral Nerve Sheath Tumors: A Systematic Review - Martin, Enrico; Acem, Ibtissam; Grünhagen, Dirk J.; Bovée, Judith V. M. G.; Verhoef, Cornelis (Frontiers in Oncology, 2020)
Background: Malignant peripheral nerve sheath tumors (MPNSTs) are complex and aggressive soft tissue sarcomas with dismal prognosis. Pathological and genetic markers may predict more aggressive behavior in MPNSTs, but have uncommonly been investigated and few are used in daily practice. This study reviews the prognostic value of immunohistochemical markers and genetic alterations in MPNST. Methods: A systematic search was performed in PubMed and Embase databases according to the PRISMA guidelines. Search terms related to ‘MPNST’ and ‘prognostic’ were used. Studies investigating the association of immunohistochemical markers or genetic alterations with prognosis were included. Qualitative synthesis was performed on all studies. Results: Forty-six studies were included after full-text screening. Sixty-seven different immunohistochemical markers were investigated: 7 differentiation markers, 2 vascularization markers, 9 receptors and ligands, 12 extracellular matrix, 10 Ras pathway proteins, 17 cell cycle regulatory proteins, 2 epigenetic modulation markers, and 8 others. Absence of S100, high Ki67, positive p53 other cell cycle proteins as well as negative H3K27me3 staining were most commonly independently associated with worse survival and disease-free survival. Several genetic alterations were investigated with varying association to survival. TP53, CDK4, RASSF1A alterations were independently associated with worse survival, as well as changes in chromosomal length in Xp, 10q, and 16p. Conclusions: MPNSTs harbor complex and heterogeneous biology. Immunohistochemical markers and genetic alterations have variable prognostic value. Complete absence of S100 and increased Ki67 can be of prognostic value. Alterations in TP53 or increase in p53 staining as well as alterations of epigenetic modulatory proteins may distinguish MPNSTs with worse outcomes. Genetic alterations and staining of other cell cycle regulatory and Ras pathway proteins may also help stratifying patients with worse outcomes. A combination of markers can increase the prognostic value.